Precise large deviations of aggregate claims in a risk model with size dependence and non stationary arrivals. Issue 3 (1st February 2018) - Fu, Ke-Ang; Li, Jie
ABSTRACT: Consider a risk model with claims of heavy tails for non stationary arrival processes that satisfy a large-deviation principle. Assume that the claim sizes and interarrival times form a sequence of random pairs, with each pair obeying a dependence structure via the conditional distribution of the interarrival time given the subsequent claim size being large, and then a precise large-deviation formula of the aggregate amount of claims is obtained.